The impact of social media interaction and customer service quality on consumer trust with customer satisfaction as a mediator - Miko Andi Wardana (Jurnal Mantik, 2024)
This research delves into the intricate relationships between social media interaction, customer service quality, and human resource management practices within the organizational context of Bali PT Towerindo Sentra Tbk. Employing a quantitative research approach, the study examines the sequential impacts of these variables on customer satisfaction, consumer trust, and employee engagement. The results reveal significant positive associations between social media interaction and customer satisfaction, as well as customer service quality and both customer satisfaction and consumer trust. Furthermore, human resource management practices are found to significantly influence organizational trust and employee engagement. These findings emphasize the strategic importance of effective social media engagement, superior customer service quality, and robust human resource management in shaping positive perceptions among customers and employees alike. The research contributes valuable insights for organizations in the telecommunications industry, offering actionable recommendations to enhance customer and employee relationships, foster trust, and fortify organizational resilience